Regional ventilation/perfusion mismatch pattern in patient with Swyer James (MacLeod's) syndrome - Sager, Sait (J Res Med Sci, 2014)
Swyer James (McLeod's) syndrome (SJMS) is an uncommon disease, which occurs as a result of childhood bronchiolitis obliterans. Patients may not be diagnosed until later in their life. A 46-year-old man underwent ventilation/perfusion scintigraphy for acute onset of dyspnea. The scan showed markedly diminished ventilation and perfusion unilaterally on the right middle and inferior lobes. However, mismatched ventilation-perfusion pattern was shown on the upper right lobe, which was consistent with pulmonary embolism. Unilaterally matched ventilation/perfusion defect can see in SJMS in lung scintigraphy; however, when pulmoner embolism may accompany, scintigraphy should be carefully examined.